The logical framework approach and development projects: The case of fondoempleo during the years 2006 to 2010 in Peru - Sueiro Cabredo, Ernesto (2021)
This research seeks to describe and analyze the disparities found in the definition of Aim and Purpose, as well as the Impact and Effect Indicators through the use of the Logical Framework Approach in the Employment Fund contests from 2006 to 2009. To do so, made a documentary review of the manuals and of the winning projects of the organisation's contests; In addition, evaluators and executors were interviewed. This allowed us to know the various contradictory connotations both in the definition and practical application, as well as the participation in poverty reduction in social projects; Examples of winning projects were also analyzed.